New species of Cryptochironomus Kieffer, 1918 (Diptera: Chironomidae: Chironominae) from Brazil - Da Silva, Fabio Laurindo; Strixino, Susana Trivinho; Oliveira, Heliana Rosely Neves (Zootaxa, 2010)
Three new species of Cryptochironomus Kieffer, 1918, C. brasiliensis, C. mantiqueira and C. reshchikovi, are described and figured as male, pupa and larva. Diagnoses for the male, pupa and larva of the genus are emended. The specimens were collected from different water systems in southeast Brazil.